Investigation of 1,4-Substituted 1,2,3-Triazole Derivatives as Antiarrhythmics: Synthesis, Structure, and Properties - Elena O. Shestakova; Sergey G. Il'yasov; Irina A. Shchurova; Vera S. Glukhacheva; Dmitri S. Il'yasov; Egor E. Zhukov; Arkady O. Bryzgalov; Tatiana G. Tolstikova; Yuri V. Gatilov (MDPI AG, 2022)
Here, we investigated the reaction of 1,3-dipolar cycloaddition of 1,3-diazido-2-nitro-2- azapropane (DANP) to propargyl alcohol over a copper-based catalyst and identified the optimum reaction conditions that enable the synthesis of 2-nitro-1,3-bis(4,4'-dihydroxymethyl)-1,2,3-triazolyl-2-azapropane (1) in more than 84% yield. The reaction between DANP, 1,5-diazido-3-nitrazapentane, and phenylacetylene produced the respective 1,2,3-triazole derivatives in 83% and 71% yields, respectively. The structures of the resultant compounds were validated by infrared and NMR spectroscopies and elemental analysis. The structure of 1 was proved by single-crystal X-ray diffraction. This study demonstrated that 1 exhibits a dose-dependent antiarrhythmic activity towards calcium-chloride-induced arrhythmia and refers to Class III: moderately hazardous substances.